Beneficial Effects of Arbuscular Mycorrhizal Fungi and Trichoderma on Diseased Shallot - Chaieydha Noer Afiefah; Suryanti Suryanti; Tri Joko; Susamto Somowiyarjo (Universitas Gadjah Mada, 2020)
Purple blotch and fusarium basal rot are important shallot diseases which have caused significant yield loss. An alternative control method for these diseases is the use of biocontrol agents, such as arbuscular mycorrhizal fungi (AMF) and Trichoderma. The objectives of this study were to determine the effects of AMF and Trichoderma sp. on shallot growth and disease suppression. The experiment was set as a Complete Randomized Block Design with three treatments and three replications. The treatments were AMF, Trichoderma sp., and control. Each treatment was applied to a row and 15 shallot plants were taken as samples for observation. Disease severity of purple blotch and fusarium basal rot, plant height, number of leaves and shallot resistances to Fusarium solani were observed during this study. Results demonstrated that at seven weeks after planting, the application of AMF and Trichoderma sp. tended to suppress fusarium basal rot to 0.89% and 1.78% respectively, but only the application of AMF that suppressed purple blotch disease to 0.44%. The application of AMF and Trichoderma sp. also tended to increase plant height, number of leaves, leaf fresh weight and dry weight, root length, and bulb weight. In addition, AMF and Trichoderma sp. application increased shallot resistances against Fusarium solani.